2015
DOI: 10.1002/ppp.1866
|View full text |Cite
|
Sign up to set email alerts
|

Do Periglacial Landscapes Exist? A Discussion of the Upland Landscapes of Northern Interior Yukon, Canada

Abstract: Much of the northern interior Yukon was never-glaciated during the Quaternary. It has experienced cold and arid conditions for several millions of years. It represents one of the closest approximations that exist today of a periglacial landscape and provides an opportunity to assess conceptual models of periglacial landscape evolution. The terrain of two upland areas, Eagle Plain and the Barn Mountains foothills, casts doubt upon the widely-assumed rapidity of periglacial landscape modification and suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…There is a tendency, moreover, to attribute all bench-like landforms on hillslopes in periglacial environments to cryoplanation (Ballantyne, 2018). Furthermore, most examples referred to in the literature appear to be relict and it has even been suggested that some such terraces are not characteristic of a periglacial environment at all, may be pre-Quaternary in age and/or may simply reflect geological structure (Büdel, 1982;French, 2016French, , 2018. Although this study is heavily reliant on morphological evidence, an advantage of the cryoplanation terraces at Svartkampan is that they are currently active, at least in part.…”
Section: Recognising Cryoplanation Terracesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a tendency, moreover, to attribute all bench-like landforms on hillslopes in periglacial environments to cryoplanation (Ballantyne, 2018). Furthermore, most examples referred to in the literature appear to be relict and it has even been suggested that some such terraces are not characteristic of a periglacial environment at all, may be pre-Quaternary in age and/or may simply reflect geological structure (Büdel, 1982;French, 2016French, , 2018. Although this study is heavily reliant on morphological evidence, an advantage of the cryoplanation terraces at Svartkampan is that they are currently active, at least in part.…”
Section: Recognising Cryoplanation Terracesmentioning
confidence: 99%
“…The processes of cryoplanation also underpin attempts to define distinctive models of periglacial hillslope and landscape evolution (cf. Peltier, 1950; Richter et al, 1963; French, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct hypotheses for CT formation are supported in contemporary literature: (1) CTs are the result of geologic structure (e.g., Waters, 1962;Hall and André, 2010;French, 2016); (2) CTs are the result of a distinctively periglacial set of weathering and transportation processes associated with snowbanks circumscribed by the term nivation (e.g., Demek, 1969;Reger and Péwé, 1976;Nelson, 1989Nelson, , 1998Nelson and Nyland, 2017;and (3) CT formation can be dependent on the presence of permafrost, and nivation can be a secondary process suite operating on these features (Matthews et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…(cf. 10 ) and concluded 9, p.298 that periglacial landscapes in geomorphic equilibrium comprise (1) cold-climate deltas currently forming at the mouths of northern rivers, (2) unglaciated Pleistocene lowlands in high northern latitudes, and (3) some ice-free areas of Antarctica.…”
mentioning
confidence: 99%